Synthesis and Anti-implantation Activity of New Stilbene Derivatives - Bandichhor, Rakeshwar; Singh, Kunwar A.; Nosse, Bernd; Tandon, Vishnu K. (Arzneimittelforschung, 2004)
New stilbene (CAS 56-53-1) derivatives have been synthesized by reductive elimination of desoxybenzoin analogs which were obtained by Fries rearrangement of the corresponding phenolic esters. The chemical structures of the compounds obtained were confirmed by 1H-NMR, IR and elemental analysis.Anti-implantation activity of the compounds was determined by performing experiments with adult male and female Spargue-Dawley rats of proven fertility.A 67 % inhibition of implantation was observed separately with compounds 3f and 3i.
Keywords: CAS 56-53-1; Estrogens, synthetic; Stilbene, anti-implantation activity, derivatives, stereoselectivity, synthesis